Indian Cultural Nationalism – Defining New Contours (Desha-shastra) - Grama Balasubramanya Harisha (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Nation and nationalism are one of the most discussed terms in modern academics and popular media. India has embraced the people, practices, cuisines, customs, faiths, rituals, religions from different parts of the world. And it is an ever growing accommodative spirit of India and its nationalism. Not ‘only, rather’ but ‘also’ is the Indian approach. It has withstood cultural colonialism in one thousand years. The cantors of India have changed with time but have not given up on culture. There fore a serious study of Indian view of nationalism as expressed by its ancient seers and modern thinkers is the need of the hour. The paper has three sections: i. Definition of Cultural Nationalism in Indian approach; ii. Some main concepts of Indian Cultural Nationalism and iii. Indian Cultural Nationalism in the contemporary time Received 9thDecember 2020; Revised 15th March 2021; Accepted 28th March 2021